Group VI metallic pillars for assembly of expanded graphite anodes for high-capacity Na-ion batteries. (30th April 2021) - Kim, You Jin; Pyo, SeongJi; Kim, Suji; Ryu, Won-Hee
Abstract: Despite the economic viability and promising potential of Na-ion batteries, their commercialization remains unrealized because of the limited intercalation of Na + ions into graphite anodes due to the large ionic radius of Na and instability of Na + ions on the interstitial sites, which result in a poor cell performance. Herein, we report a synthetic strategy for increasing the graphite interlayer distance along c -axis to facilitate the intercalation of Na + ions by embedding Group VI W metallic pillars between the graphene layers. The strong electrostatic attraction between the positively charged W 6+ ions and the negatively charged graphene oxide (GO) layers enables the assembly of the expanded graphite layers by W pillars (W-rGO) via a subsequent chemical reduction. The interlayer spacing of the reconstructed W-rGO increased to 11.1 Å, which is three-fold larger than that of graphite (3.34 Å). Consequently, the W-rGO anodes delivered an exceptionally high capacity of 678 mAh g −1 for a Na-ion battery compared with that of a pristine rGO anode (240 mAh g −1 ). Further, we elucidate the structural characteristics and electrochemical reaction mechanisms of the W-rGO anodes. This work presents a simple and effective strategy for developing high-performance carbon-based anode materials for the realization of Na-ion battery technology. Graphical abstract: Image 1 Highlights: A novel strategy to reconstruct reduced graphene oxide with W pillars. W 6+ ions facilitate restacking of negatively charged graphene oxide nanosheets. W pillars increase the interlayer space of reconstructed graphite to 11.1 Å. Expanded graphite anode with W metallic pillars delivers high specific capacity.